PENGARUH SODIUM METABISULFIT TERHADAP KENAIKAN CONSENTRATE GRADE Cu DAN PENURUNAN KANDUNGAN PYRITE - Ainun; Amirin Kusmiran; Rita Desiasni (Hexagon Jurnal Teknik dan Sains, 2020)
PT. XX is one of the largest copper company in the world. Chalcopyrite (CuFeS2), bornite (Cu5FeS3) and pyrite (FeS2) are three major minerals in PT. XX is capable to produce about 2000 tons of concentrate per day, with design of processing capacity around 120,000 tonnes per day. To obtain grade Cu concentrates, an integrated method of extraction metallurgy (metal extraction) is usually carried out, so that this study focused on increasing low consentrate grade Cu, using lime and increasing pyrite content using the flotation method by varying pH and varying the dose of sodium metabisulfite. This is indicated by the percentage of Cu grade of 12.74%, the use of lime shows the percentage reduction of 50% and the decrease in pyrite to reach a percentage of 1.16%. Of the three variations of the SMB, namely no reagent, 150 and 300 in this study, 300 is a good dose in increasing grade Cu, reducing lime use and reducing pyrite content.